2023
DOI: 10.1002/adma.202300648
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Vacancy‐Rich Piezoelectric BiO2−x Nanosheets for Augmented Piezocatalytic, Sonothermal, and Enzymatic Therapies

Abstract: Piezocatalytic therapy is a new-emerging reactive oxygen species (ROS)-enabled therapeutic strategy that relies on built-in electric field and energy-band bending of piezoelectric materials activated by ultrasound (US) irradiation. Despite becoming a hot topic, material development and mechanism exploration are still underway. Herein, as-synthesized oxygen-vacancy-rich BiO 2−x nanosheets (NSs) demonstrate outstanding piezoelectric properties. Under US, a piezo-potential of 0.25 V for BiO 2−x NSs is sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…47,48 The interference of proton (H + ) with superoxide radical yields H 2 O 2 . 49 The source of ROS is the molecular oxygen which is a strong oxidant by nature and its power of oxidation is determined by two parallel unpaired electrons which have the highest level of energy related to other electrons in the oxygen molecule. [50][51][52] Yoshio Nosaka et al clearly demonstrate the electronic states and successive transformation of its molecular entity to free radicals.…”
Section: Piezocatalysis and Consecutive Reactive Oxygen Species Gener...mentioning
confidence: 99%
“…47,48 The interference of proton (H + ) with superoxide radical yields H 2 O 2 . 49 The source of ROS is the molecular oxygen which is a strong oxidant by nature and its power of oxidation is determined by two parallel unpaired electrons which have the highest level of energy related to other electrons in the oxygen molecule. [50][51][52] Yoshio Nosaka et al clearly demonstrate the electronic states and successive transformation of its molecular entity to free radicals.…”
Section: Piezocatalysis and Consecutive Reactive Oxygen Species Gener...mentioning
confidence: 99%
“…More recently, Gai et al reported that the presence of rich OVs at the surface of BiO 2− x is favorable for H 2 O 2 adsorption, activation, and dissociation to produce reactive oxygen species (ROS). [ 36 ] Moreover, except the commonly investigated photocatalytic performance, they found that BiO 2− x nanosheets possess piezoelectric properties activated by ultrasound irradiation and exhibit peroxides and oxidase‐like activity to augment ROS production, thus providing a direction for tumor therapy. [ 36 ] In addition, Chen’ s group reported that BiO 2− x nanosheets exhibited low‐temperature thermal catalytic activity for removing 4‐chlorophenol (4‐CP), where ROS come from the release of lattice oxygen in BiO 2− x and OVs could enhance the fluidity of lattice oxygen.…”
Section: Bio2−x and Bio2‐based Photocatalystsmentioning
confidence: 99%
“…[ 36 ] Moreover, except the commonly investigated photocatalytic performance, they found that BiO 2− x nanosheets possess piezoelectric properties activated by ultrasound irradiation and exhibit peroxides and oxidase‐like activity to augment ROS production, thus providing a direction for tumor therapy. [ 36 ] In addition, Chen’ s group reported that BiO 2− x nanosheets exhibited low‐temperature thermal catalytic activity for removing 4‐chlorophenol (4‐CP), where ROS come from the release of lattice oxygen in BiO 2− x and OVs could enhance the fluidity of lattice oxygen. [ 40 ] In addition, vacancy‐rich BiO 2− x also could activate persulfate into sulfate radicals under NIR irradiation through light/heat mode due to good light‐ and heat‐absorption ability.…”
Section: Bio2−x and Bio2‐based Photocatalystsmentioning
confidence: 99%
“…In recent years, stimuli-responsive controlled nano-drug delivery systems have been proposed to improve the efficiency of treatment, while the stimulus response form included but is not limited to temperature stimuli [23][24][25], magnetism stimuli [26], enzyme stimuli [27][28][29], and pH stimuli [30]. For example, a novel multifunctional WS 2 -IO@MS-PEG nanoscale platform was prepared by the Yang group [31].…”
Section: Introductionmentioning
confidence: 99%